Agricultural corridors as ‘demonstration fields’: infrastructure, fairs and associations along the Beira and Nacala corridors of Mozambique - Gonçalves, Euclides (Journal of Eastern African Studies, 2020)
In the past decade, the Mozambican government has been mobilizing international capital to build and renovate transport infrastructure in the central and northern areas of the country, with the aim of creating agricultural corridors. Based on ﬁeld research conducted in two districts along the Beira and Nacala corridors, I examine those occasions when international capital and national agricultural policy meet smallholders in the implementation of agricultural projects. This article oﬀers a performative analysis of the constitution of agricultural corridors. I argue that agricultural corridors emerge on those occasions when international funders and investors, national elites, local bureaucrats and smallholders overstate the success of agricultural projects and constitute what I have termed ‘demonstration ﬁelds’. Regardless of the implementation of blueprints, agricultural corridors gain spatial and temporal materiality from the performance of presenting agricultural projects as successful, such as at the unveiling of agro-related infrastructure, at agricultural fairs and on occasions involving smallholders’ associations.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Beira; GP - Nampula; GP - Sofala; L - english / inglês; M - ethnography / etnografia; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
978-989-8464-46-0
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Publisher: Unpublished
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Accepted: 2016-08-26T11:02:32Z
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

JICA in Mozambique Brochure - Japan International Cooperation Agency (JICA) (2016)
1. What is JICA? Since joining the Colombo plan in 1954, Japan has been providing financial and technical assistance to developing countries through ODA (Official Development Assistance). JICA is the "one stop shop of Japan's bilateral ODA'', providing Technical Cooperation, ODA Loans (Concessional Loans) and Grant Aid. JICA has a network of more than 90 overseas offices. In Mozambique, JICA opened office in 2003. 3. Priority Areas in Mozambique: 1) Activation of Regional and Local Economies 2) Environment and Climate Change Action 3) Human Development & Capacity Building
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Imagining Agricultural Development in South–South Cooperation: The Contestation and Transformation of ProSAVANA - Shankland, Alex; Gonçalves, Euclides (World Development, 2016)
This paper discusses South–South cooperation by examining ProSAVANA, a flagship agricultural development program seeking to apply Brazilian experience to Mozambique. ProSAVANA is a joint Japan–Brazil–Mozambique initiative in the savannah zone of Mozambique’s Nacala Corridor region that was initially inspired by the Japan–Brazil PRODECER program in Brazil’s Cerrado region. ProSAVANA subsequently became the focus of fears about land-grabbing in the Nacala Corridor, attracting strong civil society contestation. We show how distinct imaginaries of agricultural development in Mozambique and Brazil were used to mobilize for and against ProSAVANA, thus revealing the contentious nature of the similarity claims underpinning South–South cooperation. In particular, we focus on the role of landscape imaginaries associated with the savannah and the Cerrado. We examine the use in the promotion and contestation of ProSAVANA of visual representations that draw on these imaginaries, including GIS maps of Mozambique’s savannah region made by Brazilian agribusiness consultants and an advocacy video of Brazil’s Cerrado region filmed by Mozambican land rights activists. Noting that the latest ProSAVANA planning documents differ significantly from those expressing its initial vision, we argue that the contestation of ProSAVANA has had a series of productive effects even before the program has moved to full implementation. These productive effects are visible not only in the program itself but also in the wider context of state-society relations shaping debates on South–South cooperation in Mozambique, Brazil, and beyond.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; M - ethnography / etnografia; Northern PEA; agriculture / agricultura; south-south cooperation / cooperação sul-sul

PEDEC-NACALA Final Study Report Analysis Report: Strategic Master Plan on Strengthening of Nacala Corridor Region-Wide Freight Network for Agricultural and Mining Sectors - Oriental Consultants Global Co., Ltd.; RECS International Inc.; International Development Center of Japan Kokusai Kogyo Co., Ltd. (Japan International Cooperation Agency (JICA), 2015)
This document was prepared as an analysis report for sharing a study result on a particular theme as part of ‘The Project for Nacala Corridor Economic Development Strategies (PEDEC-Nacala)’ which is a technical assistance project supported by Japan International Cooperation Agency (JICA) for the Government of Mozambique. PEDEC-Nacala formulated integrated development strategies for corridor development by an integrated approach involving several sectors and also by giving consideration to environmental and social aspects. The actual strategies formulated in PEDEC-Nacala and details of the present situation of the Nacala Corridor Region are compiled into the PEDEC-Nacala Final Study Report
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura

The land grabbers of the Nacala Corridor - UNAC (GRAIN, 2015)
A new report by Mozambique's National Farmers' Union (UNAC) and GRAIN shows there is a colonial-style scramble for Africa's farm lands under way. Politically-connected companies based in offshore tax havens have grabbed hundreds of thousands of hectares of farmland from peasants in Mozambique.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; Important; L - english / inglês; Northern PEA; law / direito

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

The Preparatory Survey on Nacala Port Development Project in the Republic of Mozambique Final Report - JICA (Japan International Cooperation Agency (JICA), 2011)
Japan International Cooperation Agency (JICA) decided to conduct the preparatory survey on Nacala Port Development Project in the Republic of Mozambique, and organized a survey team headed by Dr. Kobune of Ides and consists of OCDI, Oriental Consultants, ECOH CORPORATION, and Ides between June, 2010 and April, 2011. The survey team held a series of discussions with the officials concerned of the Government of the Republic of Mozambique, and conducted field investigations. As a result of further studies in Japan, the present report was finalized. I hope that this report will contribute to the promotion of the project and to the enhancement of friendly relations between our two countries. The Study Team compiled this report, which proposed the Medium and Long-term Development Plan of Nacala Port with the target year of 2030 and the Short-term Development Plan, and selected the Urgent Rehabilitation Project through close consultations with officials of the Mozambique Government, in particular, Ministry of Transport and Communications (MTC), Portos e Caminhos de Ferro de Mocambique E.P. (CFM), as well as the Management of Corredor de Desenvolvimento do Norte (CDN), and authorities concerned.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Final Report 1 of 3 Summary - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part I-II - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-IV - JICA (Japan International Cooperation Agency (JICA), 2010)
The Study Road (N13: Cuamba – Mandimba – Lichinga), as part of the two Mozambican corridors (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors), provides a strategic link to the Malawi Border at Mandimba with the ports of Nacala and Pemba, in Nampula and Cabo Delgado Provinces respectively. Although the Study Road has much potential for stimulating development and reducing poverty throughout the entire northern area of Mozambique by enabling efficient connection, the section concerned is the only unpaved section. The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-V - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors)
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part VI: Environmental and Social Considerations - JICA (Japan International Cooperation Agency (JICA), 2010)
In response to the request from the Government of the Republic of Mozambique, the Government of Japan decided to conduct the Preparatory Survey on Road Improvement Plan in Nacala Development Corridor (N13: Cuamba-Mandimba-Lichinga) and entrusted the study to the Japan International Cooperation Agency (JICA). Objectives of the study: (1) The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. (2) Formulation and recommendation of the “Regional Development Program” intended for Niassa Province is also the objective of the Study.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part IV Economic Feasibility Study - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter1 Existing Traffic Flow Patterns This chapter aims to analyze traffic flow patterns on the Study Road based on various information in order to conduct the appropriate traffic demand forecast. Chapter 2 International Goods Transportation Though Nacala Corridor This chapter aims to discuss the current condition of international goods transportation through Nacala Corridor in order to estimate future traffic demand on the Study Road. Chapter 3 Traffic Demand Forecast 3.1 Macro-Economic Background 3.2 Forecasting Methods 3.3 Traffic Demand Forecast 3.4 Results of Traffic Forecast Chapter 4 Economic and Financial Analysis (Cuamba-Mandimba Section) The Study objective is “to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing earth/ gravel roads in the rural areas to paved roads.” For the purpose of the economic evaluation, it is important to first define the existing state of the Project road for the base case, and then to define the alternatives to be analyzed, and finally the structure of the analysis.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part V Cross-Border Facilities - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter 1 Mozambique-Malawi Border Control and Facilities 1.1 Current Condition of Cross-Border Traffic between Mozambique and Malawi 1.2 Border Facilities between Mozambique and Malawi 1.3 Border Control System and Border Facilities Chapter 2 Mandimba Border Control and Facilities 2.1 Characteristics of Mandimba Border Area 2.2 Cross-Border Traffic and Cargo 2.3 Mandimba Border Post and Facilities 2.4 Chiponde Border Post and Facilities Chapter 3 Strategy for Upgrading Border Control and Facilities 3.1 SADC-COMESA Regional Strategy 3.2 One Stop Border Posts 3.3 Mozambique-Malawi Bilateral Strategy Chapter 4 Implementation Approach for Upgrading Mandimba Border Facilities 4.1 Needs Assessment and Proposed Approach for Implementation 4.2 Methodology for OSBP Phased Introduction 4.3 Challenges to OSBP Introduction Chapter 5 Border Development Strategy for Upgrading Mandimba Border Facilities 5.1 Traffic Demand Forecast at Mandimba-Chiponde Border 5.2 Proposed Implementation Policy 5.3 Proposed Facility Planning for Phased Introduction of OSBP
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura